2013
DOI: 10.1016/j.rboe.2012.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Knee ligament injuries: biomechanics comparative study of two suturetechnique in tendon – analysis “in vitro” tendon of bovine

Abstract: Objective To evaluate and compare the biomechanical behavior of two different suture configurations:“X”and“Loop”in the preparation of tendons for knee ligament reconstruction. Methods We used common digital extensor tendons of bovine that can replace the human flexor tendons in experimental studies of traction. In the first group, point “X” suture with Ethibond ® No. 5 began in the distal graft points transfixing, with spacing of 7.5 mm points… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…When comparing two tendon-suturing techniques [12], it was found that the stitch in the "Loop" presented a significantly greater mean maximum rupture force than the stitch in "X". On the other hand, the results obtained in this study show that the maximum force not influenced by the gastropexy technique or by the region to which it was applied.…”
Section: Discussionmentioning
confidence: 99%
“…When comparing two tendon-suturing techniques [12], it was found that the stitch in the "Loop" presented a significantly greater mean maximum rupture force than the stitch in "X". On the other hand, the results obtained in this study show that the maximum force not influenced by the gastropexy technique or by the region to which it was applied.…”
Section: Discussionmentioning
confidence: 99%